Frequency of Electrolyte Imbalance in Ischemic Stroke Patients Presenting to Ayub Teaching Hospital Abbottabad - Atiq Ullah; Hussain Gillani, Syed Yasir; Shah, Qasim; Hussain , Nizakat; Ihsan, Nayab; Zia Ul Haq (Indus Journal of Bioscience Research, 2025)
Background: Ischemic stroke is among the major causes of morbidity and mortality worldwide. Patients with ischemic stroke commonly experience electrolyte disturbance due to ischemic injury, stress response, hormonal changes, and low dietary intake. This condition can contribute to the organ damage, raise the possibility of developing complications, and prolong hospital stay. Information regarding electrolyte disturbance in ischemic stroke patients has remained scarce, especially in the region of Abbottabad. Objective: To determine the frequency of electrolyte imbalance in ischemic stroke patients presenting to Ayub Teaching Hospital Abbottabad. Study Design: Cross sectional study. Duration and Place of Study: This study was conducted from 15 January 2025 to 15 May 2025 in the Department of Neurology, Ayub Teaching Hospital Abbottabad, Pakistan. Methodology: A total of 120 patients aged 40 to 70 years of either gender with ischemic stroke within 36 hours of onset were included. Venous blood samples were collected before administration of intravenous fluids to assess serum sodium, potassium and calcium levels. Electrolyte imbalance was labeled when serum sodium was 130 millimoles per liter or less, serum potassium was 3.5 millimoles per liter or less or serum calcium was below 2.20 millimoles per liter. Data were analyzed using Statistical Package for Social Sciences version 26. Results: The mean age of patients was 55.05 ± 8.38 years. Hypokalemia was found in 20.00% patients, hyponatremia in 30.00% patients, and hypocalcemia in 50.00% patients. Conclusion: Electrolyte imbalance is common in ischemic stroke patients, with hypocalcemia being the most frequent abnormality followed by hyponatremia and hypokalemia.